Peripheral femoral venoarterial extracorporeal membrane oxygenation as bridge to heart-lung transplant omne iter incipit primus. - Orozco‐Hernandez, Erik J.; Melnikoff, Brett; Lusby, Megan; Tallaj, Jose; Hoopes, Charles W.; Orozco-Hernandez, Erik J (Journal of Cardiac Surgery, 2020)
Heart-lung transplant (HLT) is a widely accepted modality for certain patients with advanced and refractory cardiopulmonary disease. Some of these patients are critically ill on the transplant waiting list, and venoarterial extracorporeal membrane oxygenation (VA-ECMO) can be used as a bridge to transplantation. Although the experience with ECMO as a bridge to lung transplant is promising, there is limited evidence to use ECMO as a bridge to HLT. Femoral cannulation remains a concern for ambulation given the risk of bleeding and cannula complications despite studies reporting its safety. We present a case of a 56-year-old male with interstitial lung disease and severe secondary pulmonary hypertension, who was successfully bridged to HLT with ambulatory femoral VA-ECMO.